Gypsies in contemporary Egypt : on the peripheries of society - Parrs, Alexandra (The American University in Cairo Press, 2017)
In Gypsies in Contemporary Egypt sociologist Alexandra Parrs draws on two years of fieldwork to explore how Dom identities are constructed, negotiated, and contested in the specifically Egyptian national context. With an eye to the pitfalls and evolution of scholarly work on the vastly more studied European Roma, she traces the scattered representations of Egyptian Dom, from accounts of them by nineteenth-century European Orientalists to their portrayal in Egyptian cinema as belly dancers in the 1950s and beggars and thieves more recently.